THE DEVELOPMENT OF TEXTILE WOUND COATING WITH ACREMONIUM CHRYSOGENUM PROTEASE C - I. I. Романовська; С. С. Декіна (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2011)
Basing on the brown marine algae Laminaria japonica Aresch «Lamidan» biogel with immobilized protease C, fixed on the textile material («double depot» effect), the wound coating with high proteolytic activity (475 U/g), prolonged action (24 h) was developed. Obtaining of enzyme stabilized form was confirmed by investigation of physico-chemical features (pH- and thermooptima, pH- and thermostability, viscosity of polymer solution with protease C). The immobilized preparation in conditions of wound content (pH 5,5) on 90% surpasses in activity free enzyme.